Pediatric pneumonia patients in Jashore city, Bangladesh: screening of drug resistance pattern and molecular identification (Bangladesh Journal of Medical Science, 2024)
Background: The most common cause of death among children is pediatric pneumonia. The increase of antibiotic abuse to treat pediatric pneumonia patients in Bangladesh is alarming for the rise of multidrug-resistant (MDR) bacteria. However, there is a dearth of research available regarding this. Hence, the current study was conducted on a pilot scale to identify the MDR bacteria from pediatric pneumonia patients by molecular approaches.Methods: Saliva  and  nasal  swab  samples  were  collected  for  3  months  (July- September  2019)  from  3children  with  suspected  pneumonia  at  two different  hospitals  in  Jashore  city,  Bangladesh.  Routine  biochemical tests were performed to identify the isolates presumptively. All isolates were  tested  for  antimicrobial  resistance  according  to  CLSI  guidelines using  17  antibiotics.  Finally,  amplified  ribosomal  DNA  restriction analysis  (ARDRA)  and  16S  rRNA  sequencing  with  phylogeny  were performed to confirm the bacteria at the species level.Results: From the samples collected from the patients, 47 isolates were obtained. The  biochemical  tests  presumptively  identified  Acinetobacter spp., as the most prevalent type, which was followed by Staphylococcus spp., and Enterobacter spp. Surprisingly, every isolate was MDR, resistant to at least four antibiotics. Cefepime and Cefotaxime showed the highest (i.e.,  100%  and  87%,  respectively)  resistance  pattern.  In  addition,  the isolates showed elevated resistance towards Amoxicillin, Vancomycin, Streptomycin,  Azithromycin,  Erythromycin,  Norfloxacin,  and Tetracycline. On the contrary, they were susceptible to Imipenem and Meropenem. Subsequently, the isolates were typed into three different groups by ARDRA; the strains Acinetobacter baumannii, Enterobacter hormaechei, and Staphylococcus pasteuri were confirmed.Conclusion: The  rapid  revolution  of  multidrug  resistant  organisms  has  an  impact on morbidity, mortality and healthcare associated cost. Unrestricted use  of  antibiotics  should  be  stopped  and  surveillance  is  necessary  for controlling the emergence of resistant bacteriaBangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 729-738